"The experiences and needs of persons with disabilities in using paratransit services". Issue 4 (October 2022) - Egger, Selina Marita; Gemperli, Armin; Filippo, Martina; Liechti, Ronald; Gantschnig, Brigitte Elisabeth
Abstract: Background: Persons with disabilities do not yet experience equality with the rest of the population when using transportation. Paratransit services take over transportation for persons with disabilities when public transportation cannot be used or can only be used to a limited extent. The usefulness of these services remains limited due to financial and structural reasons. Objective: This study aims to identify the experiences of persons with disabilities with paratransit in Switzerland, explores their needs and verifies facilitators and barriers to the use of paratransit services. Furthermore, perceived experiences of how barriers and facilitators of transportation influence the participation in different areas of life of these persons are examined. Methods: In this study, we adopted a qualitative approach with four online focus group discussions and one physically present discussion group, including 31 participants overall. We collected data between July and October 2021 and analyzed the data using content analysis according to Mayring (2015). Results: Overall, persons with disabilities experience paratransit as important and appreciated this alternative to public transportation. Specifically, the services' need is individual for each person and depends on different facilitating factors (e.g., habits, health condition, activities, safety, accessibility, service) and barriers (e.g., costs, weather conditions). Conclusions: The need for paratransit services is highly individual and impacts participation in different life areas. On one hand, the federalist system in Switzerland supports a local and cultural embedment, but on the other hand leads to difficulties concerning transportation beyond the close local environment and for longer distances.